Two FAST multiplex real-time PCR reactions to assess the presence of genetically modified organisms in food. (15th February 2019) - Cottenet, Geoffrey; Blancpain, Carine; Sonnard, Véronique; Chuah, Poh Fong
Highlights: A GMO screening performed in 2 multiplex real-time PCR reactions only. 100% of cultivated GM-events successfully detected. Real-time PCR run performed in FAST mode delivering results in 40 min. Method sensitivity between 4 and 18 DNA copies. Reliability successfully tested on 20 proficiency test samples. Abstract: Methods to detect the presence of genetically modified organisms (GMOs) are evolving constantly to comply with legislation and include new transgenic traits developed by biotechnology companies. Since traditional screening methods target only a limited number of markers, not all GM-events can be detected easily. To cover a broader range, a new GMO screening method was developed, based on two real-time PCR reactions, targeting i) six major GM-markers and ii) six GM-events that do not contain these markers. This method used the FAST PCR technology and allowed a further reduction in time-to-result. Using a wide array of reference materials and proficiency test samples, the method showed a broad screening capacity and the absolute limit of detection was consistently below 20 copies, thereby demonstrating the method is fit-for-purpose.